Cloning of a putative human oncogenic virus, BK - Olliver, Caroline Louise (Department of Medicine, 2023)
Papova viruses are a group of non-enveloped icosahedral viruses which contain a double-stranded circular DNA genome in the supercoiled configuration. There are two subgroups, i.e., the papilloma and the polyoma viruses. The papilloma viruses are generally larger than the polyoma-viruses, having a genome of approximately 5 x 106 daltons compared with 3,3 x 106 daltons, and virions of approximately 55nm diameter as opposed to 41nm. The papilloma viruses generally produce benign epithelial proliferations in the host e.g., the human wart, and attempts to propagate these viruses in cells in culture have been unsuccessful. On the other hand, polyoma viruses can usually be propagated in tissue culture and do not appear to be associated with any widespread pathology in their natural hosts. Although there is no convincing evidence of polyoma viruses causing malignancies in their natural host, nonpermissive cells of other species may be transformed and these viruses therefore have oncogenic potential in particular laboratory animals. Polyoma . viruses infect eukaryotic cells, and investigation thereof should allow further elucidation of eukaryotic gene expression and regulation. Members of the polyoma group which have been extensively studied include polyoma virus itself, which infects mice, simian virus 40, (SV40),which infects rhesus monkey cells, and RKV which infects rabbits. Interest in this polyoma group of viruses has increased ever since 1965 when a new papovavirus strain, JC, was isolated from brain glial cells of a patient with progressive multifocal leukoencephalopathy (PML) and was thus the first polyomavirus infection of humans to be discovered. (ZuRhein and Chou, 1965). In 1971, an immunologically distinct polyomavirus, BK, was isolated from the urine of an immunocompromised recipient of a renal allograft (Gardner et al., 1971). Interest in these two viruses in particular has been compounded by their potential oncogenicity in humans, (see section 1.8).